Pengaruh Brand Image, Variasi Produk, dan Price Fairness terhadap Kepuasan Pelanggan Pada Kopi Kenangan di Kota Kediri - Theresia Wulandari (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to determine the influence of brand image variables, product variety and price fairness on purchasing decisions at Kopi Kenangan. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the brand image t test (X1) have a partially significant effect on purchasing decisions. Product innovation (X2) has a partially significant effect on purchasing decisions. Price Fairness (X3) has a partially significant effect on Purchasing Decisions. Promotion (X4) has a partially significant effect on Purchasing Decisions. The results of the F test can be concluded that brand image, product innovation and price fairness simultaneously and significantly influence purchasing decisions at Kopi Kenangan.